Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Morinda officinalis polysaccharide improves osteoporosis by enhancing m⁶A-modified SOCS5 mRNA stability via regulating the hsa_circ_0001165/IGF2BP2 axis - ZhiBo Zhu; Yi Yang; Yi Liu; LingFeng Liao (Molecular Genetics and Genomics, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Integrating enzymatic activity into highly emissive metal-organic frameworks derived from AIE ligands via horseradish peroxidase immobilization for dual-mode optical sensing - Zuyao Fu; Lingfeng Yang; Yuanyuan Zhang; Xuanjun Zhang; Jing Xie; Zhaoyang Ding (Chemical Engineering Journal, 2026)

Interdigitated electric-magnetic gradient MXene-based nanocomposite films for concurrent high-efficiency electromagnetic shielding and sensitive detection - Lingfeng Yu; Yanni Yang; Shulong Chang; Yihao Xiao; Song Luo; Shichun Hao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Mechanisms of interlayer force transmission and slip surface penetration in pile-reinforced reservoir landslides with multi-sliding zones - Haojie Duan; Zongxing Zou; Yang Zhang; Lingfeng Wu; Jiang Li; Jianqiang Tao; Yikai Niu; Xinli Hu (Landslides, 2026)

Dynamic characterization of representative naval steels under high-velocity fragment impact and functional vulnerability assessment of naval propulsion-system components - WenCai Sun; HouXiang Wang; LingFeng Hu; YuAng Shi; JianNan Li; ZiChun Yang (Ocean Engineering, 2026)

Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

Target of contracted management rights, value orientations, and management behaviors of forest farmers in China - Fengxia Chen; Yan Xu; Yitong Yang; Lingfeng Wei (Journal of Rural Studies, 2026)

Potential predictability of global seasonal precipitation anomalies determined by climate modes - Yu Wang; Xiu-Qun Yang; Dejian Yang; Lingfeng Tao; Jiabei Fang; Xuguang Sun (Climate Dynamics, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Polystyrene microplastics impede growth and induce behavioural toxicity in endangered juvenile horseshoe crabs (Tachypleus tridentatus) - Yi Jiang; Zhiyuan Yang; Lingfeng Jiang; Cheong-Meng Chong; Shanza Gul; Youji Wang; Khor Waiho; Xiaowan Ma; Zhi Chen; Menghong Hu (Marine Environmental Research, 2026)

Environmental changes in the Okinawa Trough over the last 88 ka BP: Evidence from high-resolution bulk mineralogy - Lingfeng Luo; Xuguang Feng; Jianjun Zou; Xisheng Fang; Xinru Xue; Ruxi Dou; Baohua Han; Qingchao Wang; Aimei Zhu; Zhi Dong; Gang Yang; Xuefa Shi (Marine Geology, 2026)

Three ectomycorrhizal fungal inoculum modifies the growth performance and tolerance of Quercus nuttallii seedlings under salt stress - Nan Yang; Cheng Wan; Daoyuan Ren; Yan Zhang; Stefano Chelli; Zhengxue Zhu; Silvia Traversari; Giovanni Emiliani; Lingfeng Mao (Forest Ecology and Management, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Multiscale-reinforced high-strength MXene-based EMI shielding films with integrated electronic skin functionalities - Lingfeng Yu; Yanni Yang; Xinyu Huang; Yihao Xiao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Evaluating the propagation characteristics of meteorological drought to hydrological drought using a three-dimensional method - Xiaoli Yang; Lingfeng Xie; Ding Luo; Zhoubing Ye (Journal of Hydrology, 2025)

Urban vegetation productivity under climate change and increasing urbanization: Insights from both urban-rural comparison and trend analysis for global cities - Jiuyi Chen; Bo Qiu; Weidong Guo; Xin Miao; Yipeng Cao; Zhihan Zhao; Siwen Zhao; Lingfeng Li; Yueyang Ni; Shihan Tang; Limei Yang (Urban Forestry & Urban Greening, 2025)

Discharge and deposition metallogenic model of “Datangpo-type” manganese deposits in China: Geophysical evidence from deep electrical structure of manganese-bearing grabens - Bingnan Yang; Xiangyun Hu; Lingfeng Gao; Xiaoqing Shen; Weiyang Liao; Jiajun Wang; Liangjun Yuan (Journal of Asian Earth Sciences, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

Positive contributions of China's protected areas in biodiversity conservation and carbon storage under future climate change - Xuede Dong; Jirui Gong; Frank Yonghong Li; Lingfeng Mao; Weiyuan Zhang; Siqi Zhang; Guisen Yang; Chenyi Yan; Ruijing Wang; Shangpeng Zhang; Tong Wang (Science of The Total Environment, 2025)

Alleviating the work function of MoNi4/NiO heterostructures by stacking faults for enhanced hydrogen evolution reaction - Deli Tian; Junlin Yan; Lingfeng Yang; Min Xi; Youyu Long; Hua Zhang; Anran Chen (Chemical Engineering Journal, 2025)

Propagation characteristics of meteorological drought to hydrological drought in China - Ding Luo; Xiaoli Yang; Lingfeng Xie; Zhoubing Ye; Liliang Ren; Linyan Zhang; Fan Wu; Donglai Jiao (Journal of Hydrology, 2025)

In-situ atmospheric thermoelectric conversion on Mars - Yuzhuo Yang; Yonghao Zhang; Yu Yao; Gang Pei; Hua Tian; Lingfeng Shi; Gequn Shu (Science Bulletin, 2025)

Late Oligocene paleosols in the Haltang Basin of northeastern Tibetan Plateau and their implications for the early extent of the Asian monsoon - Zhaobin Zhang; Shuang Dai; Xinnan Fang; Xiaojun Ma; Yufan Zhang; Zhongzhao Ding; Lingfeng Qin; Chunyan Li; Meng Zhou; Tianqi Ji; Jie Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Cascade assembly of metal-organic Framework–Immobilized enzyme complexes for enhanced catalytic activity and sensing applications - Zuyao Fu; Hao Wang; Lingfeng Yang; Zhaoyang Ding; Jing Xie (Chemical Engineering Journal, 2025)

Glyceryl lignin enhances lytic polysaccharide monooxygenase (LPMO) oxidative activity via electron transfer and H2O2 generation: Mechanistic insights from glycerol pretreatment - Lingfeng Long; Han Wang; Chong Wang; Shoushuai Feng; Hailin Yang; Xianzhi Meng; Chen Huang; Arthur J. Ragauskas (Chemical Engineering Journal, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Adaptive Responses in Byssal Growth and Shedding: Insights from Pteria penguin Under Thread Trimming and Non-Trimming Conditions - Hebert Ely Vasquez; Shangkun Wei; Guoliang Yang; Lingfeng Wang; Peixuan Yu; Mingyue Dong; Chao Yuan; Xing Zheng (Journal of Marine Science and Engineering, 2025)
Bivalves use byssal threads for attachment and locomotion, periodically shedding and regenerating them. In the winged pearl oyster Pteria penguin—known for its strong byssus and its role in the pearl industry—shedding may occur when the byssal stalk reaches a critical size, although the underlying mechanism remains unclear. This study investigated whether artificial manipulation of the byssus (via trimming) could stimulate thread production and promote shedding in adult P. penguin from two size groups. Byssal threads attached to the substrate were trimmed every 3–5 days over a 30-day period and compared to untrimmed controls. Oysters with trimmed byssus produced significantly more threads, with smaller individuals outperforming larger ones in both thread count and byssal stalk diameter. Moreover, small oysters exhibited a higher frequency of complete byssal shedding. These findings suggest that trimming stimulates thread production and accelerates stalk thickening, potentially triggering shedding due to spatial constraints at the attachment site. This response appears to reflect an adaptive mechanism for maintaining effective attachment and may help explain how mechanical or environmental cues influence byssal dynamics. Understanding this process offers new insight into the behavioral and physiological plasticity of P. penguin, with potential applications in pearl oyster management and aquaculture.

Co-infection by RGNNV and V. rotiferianus in golden pompano: Insights into disease risks and immune responses - Xinshuai Li; Lingfeng Guan; Cuiyu Liu; Jinpeng Chen; Xin He; Yanwei Li; Shaowen Wang; Qiwei Qin; Min Yang (Aquaculture, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Co-infection of nervous necrosis virus and Vibrio harveyi increased mortality and worsened the disease severity in the orange-spotted grouper (Epinephelus coioides) - Lingfeng Guan; Xinshuai Li; Jinpeng Chen; Liqun Wang; Xinyue Zhang; Hongyan Sun; Yanwei Li; Min Yang; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

A robust index was extracted to assess the prolonged changes in debris flow activity after a high magnitude earthquake - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Jiangang Chen; Tao Yang; Lingfeng Gong; Ming Chen; Qingyun Shi; Ning Li (CATENA, 2025)

Processes determining the seasonality of accelerated Tibetan Plateau warming during recent decades - Mengchu Zhao; Xiu-Qun Yang; Lingfeng Tao; Jing-Jia Luo (Climate Dynamics, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Causes of Atypical Meiyu in the Lower Yangtze River Basin in 2022: Subseasonal Perspective and Predictions - Zhiqi Zhang; Ping Liang; Yajing Liu; Yang Wu; Lingfeng Tao; Qi Chen; Yihui Ding (Journal of Meteorological Research, 2025)

Land–air interaction maintaining the tripole pattern of anomalous Eurasian blocking activities during the Meiyu season - Zitian Xu; Xiu-Qun Yang; Linyuan Sun; Lingfeng Tao (Climate Dynamics, 2025)

Portable sensing of hydrogen peroxide using MOF-based nanozymes - LingFeng Yang; Zuyao Fu; Jing Xie; Zhaoyang Ding (Food Research International, 2024)

Urbanization significantly increases greenhouse gas emissions from a subtropical headwater stream in Southeast China - Mutan Dai; Yuanhui Xu; Yegenberdy Genjebay; Lingfeng Lu; Chuan Wang; Hao Yang; Changchun Huang; Tao Huang (Science of The Total Environment, 2024)

Ball milling nano-sized biochar: bibliometrics, preparation, and environmental application - Lingfeng Zeng; Jiezhi Ma; Jie Yang; Jian Yang; Xiangzhou Zeng; Yaoyu Zhou (Environmental Science and Pollution Research, 2024)

Effect of propranolol on pharmacokinetics of clozapine in schizophrenic patients: a meta-analysis - Xiding Yang; Qiangyong Yan; Lingfeng Yang; Jingjing Li; Xiao Fan; Jindong Chen; Haishan Wu; Yongyu Yang; Ronghua Zhu; Pingfei Fang (European Journal of Clinical Pharmacology, 2024)

Recent advances on environmental behavior of Cu-based nanomaterials in soil-plant system: A review - Jieyu Gao; Yi Zhu; Lingfeng Zeng; Xin Liu; Yuan Yang; Yaoyu Zhou (Journal of Environmental Management, 2024)

Wide-bandgap donor polymers from organic photovoltaics as dopant-free hole transport layers for perovskite solar cells - Hongtao Lai; Xin Yang; Liujiang Zhang; Leyu Bi; Binqiang Tian; Huanhuan Wang; Xingyu Gao; Lingfeng Lu; Bin Kan; Xiaofei Ji; Qiang Fu (Chemical Engineering Journal, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

Current progress on manganese in constructed wetlands: Bibliometrics, effects on wastewater treatment, and plant uptake - Lingfeng Zeng; Xin Liu; Jiezhi Ma; Jie Yang; Jian Yang; Yaoyu Zhou (Environmental Research, 2024)

Differentiation of fungal trophic guilds to long-term nitrogen addition in a poplar plantation - Nan Yang; Jiangbao Zhang; Jiani Hua; Baohan Song; Tianyi Wang; Wei Xing; Guobing Wang; Lingfeng Mao; Honghua Ruan (Forest Ecology and Management, 2024)

Valorization of straw biomass into lignin bio-ink, bacterial cellulose and activated nanocarbon through the trade-off alkali-catalyzed glycerol organosolv biorefinery - Lingfeng Long; Jinkang Chen; Yueqin Cao; Chen Huang; Shoushuai Feng; Hailin Yang; Dong Tian (Chemical Engineering Journal, 2024)

Wintertime ocean–atmosphere interaction processes associated with the SST variability in the North Pacific subarctic frontal zone - Qionghui Huang; Jiabei Fang; Lingfeng Tao; Xiu-Qun Yang (Climate Dynamics, 2024)
Recent research indicates that the midlatitude oceanic frontal zones are the key regions of ocean–atmosphere interaction. The thermal condition of midlatitude ocean in frontal zones can affect the atmosphere efficiently through both diabatic heating and transient eddy feedback. In this study, the wintertime SST variability in the subarctic frontal zone (SAFZ) of the North Pacific and the associated ocean–atmosphere interaction mechanism are examined based on observational and theoretical analyses. It is found that the SAFZ-related SST anomaly is characterized as a large-scale interannual mode that can persist during the whole winter, and that its evolution is accompanied with local ocean–atmosphere interaction processes. The initial anticyclonic surface wind anomaly associated with the weakened Aleutian Low forces a large-scale warm SST anomaly in midlatitude North Pacific by driving northward Ekman flow and downward heat flux. With the increase of SST anomaly, the air-sea heat flux exchange reverses, indicating that the ocean starts to heat the atmosphere. In addition to increasing the diabatic heating, the warm SST anomaly strengthens the SST gradient in the north part of SAFZ. The low-level atmospheric baroclinicity is adjusted to synchronize with the SAFZ correspondingly due to oceanic thermal influence, causing change of transient eddy activities. Though all the ocean-induced diabatic heating, transient eddy heating and transient eddy vorticity forcing are enhanced over SAFZ, the last physical process plays the most important role in shifting and maintaining the equivalent barotropic atmospheric circulation anomalies. Therefore, the ocean–atmosphere interaction provides a mechanism for the development and maintenance of SAFZ-related anomalies of the North Pacific ocean–atmosphere system throughout the winter.

Improving the long-term performance of electric vehicles CO2 heat pump through correcting discharge pressure - Yuzhuo Yang; Lingfeng Shi; Hua Tian; Gequn Shu (Journal of Cleaner Production, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

Grouper Rab1 inhibits nodovirus infection by affecting virus entry and host immune response - Lingfeng Guan; Xiaozhi Wen; Zihan Zhang; Liqun Wang; Xinyue Zhang; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Interfacial electronic engineering of heterostructured Co2P-MoNiP/NF nano-sea-urchin catalysts for efficient and stable hydrogen evolution via water/seawater splitting - Yifan Zhao; Hua Zhang; Ji Chen; Shuwen Zhao; Min Xi; Lingfeng Yang; Youyu Long; Zitao Ni; Yao Zhou; Anran Chen (Chemical Engineering Journal, 2023)

An improved frequency-domain model for the supercritical flow instability analysis in vertical tubes - Lingfeng Bi; Xirong Zhang; Weiteng Li; Tingyu Chen; Xiaocheng Du; Dong Yang (Annals of Nuclear Energy, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Revisiting the East Asian summer monsoon structure: a combined effect of condensational heating and synoptic eddy activities - Shengjie Chen; Xiu-Qun Yang; Jiabei Fang; Linyuan Sun; Lingfeng Tao; Xiaozhuo Sang; Manman Yin (Climate Dynamics, 2023)

Quantifying the processes of accelerated wintertime Tibetan Plateau warming: outside forcing versus local feedbacks - Mengchu Zhao; Xiu-Qun Yang; Lingfeng Tao (Climate Dynamics, 2023)

Impact of anomalous Eurasian blocking activities on the East Asian Meiyu rainfall - Zitian Xu; Xiu-Qun Yang; Lingfeng Tao; Linyuan Sun (Climate Dynamics, 2023)

Compound hot extremes exacerbate forest growth decline in dry areas but not in humid areas in the Northern Hemisphere - Hongjun Yang; Wenjing Tao; Qimei Ma; Hanfeng Xu; Lingfeng Chen; Hongjun Dong; Yuchuan Yang; Nicholas G. Smith; Lei Chen (Agricultural and Forest Meteorology, 2023)

Performance of potentiometric oxygen sensors with LSCF electrode in lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Lingfeng Yang; Muran Qi; Xiaobo Li; Yifeng Wang; Zhenhua Sheng; Xu Tu; Gaoxiang Xu; Boqing Li; Hao Wu; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Phylogenomic resolution of Imparidentia (Mollusca: Bivalvia) diversification through mitochondrial genomes - Yu Wang; Yi Yang; Lingfeng Kong; Takenori Sasaki; Qi Li (Marine Life Science & Technology, 2023)
Despite significant advances in the phylogenomics of bivalves over the past decade, the higher-level phylogeny of Imparidentia (a superorder of Heterodonta) remains elusive. Here, a total of five new mitochondrial sequences ( Chama asperella , Chama limbula , Chama dunkeri , Barnea manilensis and Ctena divergens ) was added to provide resolution in nodes that required additional study . Although the monophyly of Lucinida remains less clear, the results revealed the overall backbone of the Imparidentia tree and the monophyly of Imparidentia. Likewise, most relationships among the five major Imparidentia lineages—Lucinida, Cardiida, Adapedonta, Myida and Venerida—were addressed with a well-supported topology. Basal relationships of Imparidentia recovered Lucinidae as the sister group to all remaining imparidentian taxa. Thyasiridae is a sister group to other imparidentian bivalves (except Lucinidae species) which is split into Cardiida, Adapedonta and the divergent clade of Neoheterodontei. Neoheterodontei was comprised of Venerida and Myida, the former of which now also contains Chamidae as the sister group to all the remaining venerid taxa. Moreover, molecular divergence times were inferred by calibrating nine nodes in the Imparidentia tree of life by extinct taxa. The origin of these major clades ranged from Ordovician to Permian with the diversification through the Palaeozoic to Mesozoic. Overall, the results obtained in this study demonstrate a better-resolved Imparidentia phylogeny based on mitochondrial genomes.

Quenching-induced surface reconstruction of perovskite oxide for rapid and durable oxygen catalysise - Lingfeng Ke; Shengli Pang; Chao Long; Ting Fang; Gongmei Yang; Yifan Song; Xudong He; Shuai Ma; Yaozheng Qian; Xiangqian Shen; Chonglin Chen (Chemical Engineering Journal, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Experimental study on failure law of subgrade concrete with different damage base - Xiangfeng Lv; Lingfeng Meng; Xin Lin; Xuan Ji; Yahan Yang (European Journal of Environmental and Civil Engineering, 2023)

Interaction among soil nutrients, plant diversity and hypogeal fungal trophic guild modifies root-associated fungal diversity in coniferous forests of Chinese Southern Himalayas - Nan Yang; Yan Zhang; Jingji Li; Xiuxiu Li; Honghua Ruan; Parag Bhople; Katharina Keiblinger; Lingfeng Mao; Dong Liu (Plant and Soil, 2022)

Ecosystem Services of Ecosystem Approach to Mariculture: Providing an Unprecedented Opportunity for the Reform of China’s Sustainable Aquaculture - Xijie Zhou; Jinghui Fang; Siyuan Shi; Ling Yang; Bin Xie; Lingfeng Huang (Frontiers in Marine Science, 2022)
China is the biggest provider of mariculture products, and the industry is still growing rapidly. Increasing scientific evidence indicates that mariculture may provide valuable ecosystem goods and services in China. Here, we performed a systematic literature review of studies with the aim of understanding the ecosystem services of mariculture and a comprehensive review of ecosystem approaches that may improve mariculture ecosystem services and goods in China. We highlight four ecosystem services functions in China, including food supply, nutrient extraction, carbon sequestration, and biodiversity conservation. Given the further reform of China’s mariculture, we outlined several ecosystem approaches including integrated multi-trophic aquaculture (IMTA), carrying capacity assessment and monitoring, marine spatial planning, and waste treatment and recirculating mariculture system. We conclude that the ecosystem services of the ecosystem approach to mariculture provide an unprecedented opportunity for the reform of China’s sustainable aquaculture. Finally, a synthesis of sustainable development of mariculture, along with the five recommendations for future mariculture development in China, is outlined.

A climate perspective of the quasi-stationary front in southwestern China: structure, variation and impact - Danping Cai; Lingfeng Tao; Xiu-Qun Yang; Xiaozhuo Sang; Jiabei Fang; Xuguang Sun; Weiping Wang; Hongming Yan (Climate Dynamics, 2022)
Yunnan–Guizhou quasi-stationary front (YGQSF) is a unique weather phenomenon that frequently occurs during the winter half year over the Yunnan–Guizhou Plateau in southwestern China. Most of the previous studies analyzed it only with synoptic cases. This study investigates the structure, variation, and impact of this front from a climate perspective, using long-term high-resolution atmospheric reanalyses and high-density station records for 1981–2016. An objective method quantifying YGQSF is proposed and three indexes are defined to measure its intensity, frequency, and location, respectively, with horizontal gradient of air potential temperature at a terrain-following level of sigma 0.995. With these indexes, climatological structure, subseasonal variability as well as climatic impact of the front are comprehensively examined. In climatology, YGQSF as a north–south-oriented low-level front is found to occur the most frequently during January–February–March, determined predominately by the coldness from the east of the front. The structure of the front identified essentially reflects an obstruction of high-terrain Yunnan (the western part of the plateau) to the low-level cold air mass, which makes near-surface cold northeasterly winds cease westward intruding and veer upward over relatively low-terrain Guizhou, transporting moisture upward and forming low clouds. A sharp climate contrast is thus formed between two sides of the front: cold, sunless, and continuously rainy Guizhou versus warm and sunny Yunnan. Furthermore, the front features significant subseasonal variations with periods at around 30 days and 60 days largely in its intensity. Anomalously strong YGQSF events which are caused 75% by the cold anomaly from the east but no more than 17% by the warm anomaly from the west yield different anomalous structures, but consistently amplify the sharp climate contrast between Yunnan and Guizhou.

Evaluation of synoptic eddy activities and their feedback onto the midlatitude jet in five atmospheric reanalyses with coarse versus fine model resolutions - Xiaozhuo Sang; Xiu-Qun Yang; Lingfeng Tao; Jiabei Fang; Xuguang Sun (Climate Dynamics, 2022)
Interaction between synoptic eddy and mean flow plays a crucial role in maintaining midlatitude westerly jet. In this study, climatologies of synoptic eddy activities and their feedback onto midlatitude jet for 1980–2016 are evaluated and compared through analyzing daily data from five atmospheric reanalyses with different resolutions including one coarse-resolution reanalysis (NCEP2) and four fine-resolution reanalyses (ERA-Interim, JRA-55, MERRA-2, and CFSR). Horizontal resolutions of the atmospheric models generating those reanalyses are approximately equivalent to 210, 79, 60, 50, and 38 km, respectively. Results show that the eddy activities and their feedback onto the midlatitude jet in those fine-resolution reanalyses are consistently and significantly stronger than those in the coarse-resolution reanalysis (NCEP2). The maximal relative increases that are found to occur primarily in the midlatitudes of the Southern Hemisphere are estimated to be up to 55% for the baroclinicity, 53% for the eddy energetics, 59% for the eddy forcing, and even 85% for the eddy feedback onto the mean flow. Those increases are reasonably conjectured to be related to increased model resolutions, since the synoptic eddy genesis is proportional to the low-level atmospheric meridional temperature gradient which is sensitive to the meridional resolution of atmospheric models. Although the coarse-resolution reanalysis resolves synoptic eddies insufficiently and thus underestimates their feedback onto the mean flow, the magnitudes of eddy-driven jets are almost the same among five reanalyses, implying a mismatch between the eddy feedback and the eddy-driven jet in the coarse-resolution reanalysis. Therefore, the results of this study imply the importance of using fine-resolution reanalyses in accurately understanding the midlatitude synoptic eddy–mean flow interaction.

Decadal changes of wintertime poleward heat and moisture transport associated with the amplified Arctic warming - Xiaozhuo Sang; Xiu-Qun Yang; Lingfeng Tao; Jiabei Fang; Xuguang Sun (Climate Dynamics, 2022)

Erratum to: Contribution of Water Vapor to the Record-Breaking Extreme Meiyu Rainfall along the Yangtze River Valley in 2020 - Licheng Wang; Xuguang Sun; Xiu-Qun Yang; Lingfeng Tao; Zhiqi Zhang (Journal of Meteorological Research, 2021)

Study on bioleaching of heavy metals and resource potential from tannery yard sludge - Hang Liu; Kaizhi Yang; Lingfeng Luo; Qian Lu; Yonggui Wu; Meiyan Lan; Youfa Luo; Wan Liang (Environmental Science and Pollution Research, 2021)

Contribution of Water Vapor to the Record-Breaking Extreme Meiyu Rainfall along the Yangtze River Valley in 2020 - Licheng Wang; Xuguang Sun; Xiuqun Yang; Lingfeng Tao; Zhiqi Zhang (Journal of Meteorological Research, 2021)

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes - Yu Wang; Yi Yang; Hongyue Liu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Zoologica Scripta, 2021)
Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the protein‐coding gene order revealed a highly conserved pattern among the same subclade lineages. According to our molecular analyses, Tapetinae should be recognized as a valid subfamily, but the genera formed para‐polyphyletic clades. Chioninae was recovered not monophyletic that differs from a previously molecular phylogeny. Furthermore, the reconstructed chronogram calibrated with fossils recovered the Veneridae have originated during the early Permian (about 290 million years ago). Noticeably, programmed frameshift was found in the nad4 gene of Leukoma jedoensis , Anomalodiscus squamosus and Antigona lamellaris and cob gene of L. jedoensis . This is the first time that the presence of the programmed frameshift has been found in the protein‐coding genes of Heterodonta species. Our results improved the phylogenetic resolution within Veneridae, and a more taxonomic sampling analysis of the subfamily Chioninae is supposed to construct.

Mitogenomic phylogeny of Trochoidea (Gastropoda: Vetigastropoda): New insights from increased complete genomes - Erfei Guo; Yi Yang; Lingfeng Kong; Hong Yu; Shikai Liu; Zhanjiang Liu; Qi Li (Zoologica Scripta, 2021)
Increased mitochondrial (mt) genomes can provide more sets of genome‐level characteristics for resolving deeper phylogeny. Limited information with respect to the Trochoidea mitochondrial genome organization is available; besides, monophyly and internal relationships of the superfamily still remain a matter of discussion. To resolve the monophyly and internal phylogenetic controversies of Trochoidea and expand our understanding for mt genomic characteristic evolution among Trochoidea, the phylogenetic trees were reconstructed using 13 newly sequenced complete mt genomes and 35 genomes from GenBank, and both the maximum likelihood and Bayesian inference analyses were highly supported. Vetigastropoda phylogenetic analyses recovered the monophyly of Trochoidea. Trochoidea phylogenetic analyses and genetic distances supported the non‐monophyly of Tegulidae and Tegula , indicating that the taxonomic status of several genera ( Rochia , Tectus and Cittarium ) should be revised and Tegula , Omphalius and Chlorostoma should be placed as a same genus. The close affinity between Tectus virgatus and Rochia was also revealed. Three‐nucleotide insertion in nad1 , nine‐nucleotide insertion and six‐nucleotide deletion in nad5 are detected in Tegulidae, Tectus and Rochia , respectively. Gene orders within Trochoidea are stable, with gene rearrangements exclusive to tRNA genes observed. Homoplasious convergences because of trnT rearrangement display translocation in Turbinidae and reversion in Trochidae and Calliostomatida. For trnE and trnG , we identify 11 arrangement types, suggesting that the gene rearrangement history needs to be further evaluated. Our study emphasizes the importance of mt genomes in resolving phylogenetic relationships within Trochoidea. In addition, the mt genomic characters would contribute new insights into the classification of Trochoidea.

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.

Mitogenomic phylogeny of Nassarius (Gastropoda: Neogastropoda) - Yi Yang; Qi Li; Lingfeng Kong; Hong Yu (Zoologica Scripta, 2019)
Nassariids (Family Nassariidae) are a group of marine snails that are distributed worldwide, with their maximum species diversity in tropical regions, particularly the Indo‐Pacific. However, the traditional taxonomy of Nassariidae defined by shell or radula characters is usually inconsistent with little phylogenetic signal. In the present study, the complete mitochondrial (mt) genomes of nine Nassarius species were sequenced and compared with other eight nassariid species previously reported. All nassariid mt genomes showed the same gene order as in most caenogastropods and shared a very similar pattern with respect to genome size, nucleotide composition and AT contents. A deletion of three nucleotides in nad6 gene was detected in Nassarius jacksonianus and Nassarius acuticostus , and this feature also provided implications for nassariid phylogeny. The genetic distance analysis and reconstructed phylogeny revealed a distant relationship between N . jacksonianus or N. acuticostus and other members in Nassarius . The mitogenomic phylogeny recovered the evolutionary relationships within Nassarius with high statistical support. In addition, a chronogram was reconstructed under an uncorrelated relaxed molecular clock, which dated the divergence among main lineages of Nassarius during ~31 MYA.

Identification, evolution and expression analyses of Ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit gene family in wheat (Triticum aestivum L.) - Lingyue Qin; Yuanxia Xue; Ying Fei; Lingfeng Zeng; Shushen Yang; Xiping Deng (Acta Physiologiae Plantarum, 2018)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Mitogenome evidence for the existence of cryptic species in Coelomactra antiquata - Yang Yuan; Lingfeng Kong; Qi Li (Genes & Genomics, 2013)

The complete mitochondrial genome of the grand jackknife clam, Solen grandis (Bivalvia: Solenidae): a novel gene order and unusual non-coding region - Yang Yuan; Qi Li; Lingfeng Kong; Hong Yu (Molecular Biology Reports, 2012)

Gametogenic cycle and biochemical composition of the clam Mactra chinensis (Mollusca: Bivalvia): Implications for aquaculture and wild stock management - Qi Li; Lin Yang; Qiaozhen Ke; Lingfeng Kong (Marine Biology Research, 2011)

Genetic Structure of the Veined Rapa Whelk (Rapana venosa) Populations Along the Coast of China - Jianmin Yang; Qi Li; Lingfeng Kong; Xiaodong Zheng; Rucai Wang (Biochemical Genetics, 2008)